2013
DOI: 10.1186/1477-7819-11-41
|View full text |Cite
|
Sign up to set email alerts
|

Lateral supraorbital approach applied to sellar tumors in 23 consecutive patients: the Suzhou experience from China

Abstract: BackgroundPituitary adenoma, craniopharyngioma and meningioma are common sellar lesions, accounting for more than 90% of sellar tumors. The aim of this study is to assess the reliability and safety of the lateral supraorbital (LSO) approach to remove sellar tumors.MethodsBetween June 2011 and December 2011, 23 patients with neoplastic lesions underwent surgery by the corresponding author (ZW) via the LSO approach. The clinical presentations, neuroradiological findings, microsurgical techniques, and outcome at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Craniotomy was done by lateral supraorbital approach (LSO) for complete tumor excision. 26 After surgery, and before discharging from hospital, the patient was re-examined with MRI and CT scan. Results of re-examination revealed that the tumor was totally removed.…”
Section: Case Report Case Historymentioning
confidence: 99%
“…Craniotomy was done by lateral supraorbital approach (LSO) for complete tumor excision. 26 After surgery, and before discharging from hospital, the patient was re-examined with MRI and CT scan. Results of re-examination revealed that the tumor was totally removed.…”
Section: Case Report Case Historymentioning
confidence: 99%
“…Laterally we find the clinoid processes, the internal carotid and the posterior communicating arteries; posteriorly we identify the pituitary stalk, infundibulum, and the Lillequist membrane; superiorly, we have the optic chiasm, the lamina terminalis, and the anterior cerebral artery complex. 4 The space is quite small, (mean length 8mm, mean width 11mm), and the path of least resistance for tumor growth tends to be over the planum sphenoidale (anteriorly), the optic nerves into the optic canals (laterally), above the chiasma, displacing it superiorly, or down over the tuberculum and sellae (inferiorly) as shown in Figure 1. Table 1 shows the distribution of tumor size and levels of recovery of the 25 patients with visual impairment.…”
Section: ■ Resultsmentioning
confidence: 99%
“…7 Several surgical approaches such as subfrontal, bifrontal, unilateral frontal, supraorbital keyhole, pterional have been proposed for the resection of TSM, and more recently the neurosurgical endoscopic techniques have been introduced as a visualization option during removal of skull base tumors, both transcranially and endonasally. 4 The aim of this paper is to report our case series, with special emphasis on different surgical approaches for TSM and their advantages and complications.…”
mentioning
confidence: 99%
“…Chen ve ark. [17] ortalama 9,6 aylık takibi olan 6 vakalık serisinde total rezeksiyon %83,3, nüks %0, mortalite %16,6 olarak bildirilmektedir. Palani ve ark.…”
Section: Discussionunclassified